The Economic Impact of Inflation and Exchange Rates on Stock Returns Mediated by Capital Structure in Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange - Peni, Katarina Ina; Hermuningsih, Sri; Damanik, Johanes Maysan (Yayasan Riset dan Pengembangan Intelektual, 2025)
In this study examines the effect of inflation and exchange rates on stock returns with capital structure as a mediating variable in food and beverage subsector companies listed on the Indonesian Stock Exchange during 2019-2023. The results showed that inflation and exchange rates have a signnificant influence on capital structure, where inflation has a negative impact and exchange rate fluctuations worsen capital structure. Furthermore, inflation has a positive impact on stock returns while exchange rates have a negative impact. Capital structure is proven to have a positive impact on stock returns, indicating the importance of good capital structure management in improving investor perception and stock performance. These results provide important insights for economic risk management and invesment in the sector.